Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Q1.

$$\sum\limits_{j=0}^{N-1} \sum\limits_{i=0}^{N-1} \sum\limits_{y=0}^{j} \sum\limits_{x=0}^{i} a(x)a(y)b(|x-y|) $$

Given that $b(0) = 0$, Find the coefficient of $b(k)$, $0\le k \le N-1$ in the above expansion.

Q2. $$\sum\limits_{j=0}^{N-1} \sum\limits_{i=0}^{N-1} \sum\limits_{x=0}^{\min(i,j)} a(x) .$$

Find the coefficient of $a(x)$ in the above expansion?

share|improve this question
    
Is this homework? –  Brian Mar 16 '11 at 12:36
    
You've been a member for over 4 months now. Yet you are still making posts (i) in the imperative mode; and (ii) with no motivation. –  Arturo Magidin Mar 16 '11 at 19:02
    
Did you get something out of the answer below? –  Did Apr 7 '11 at 8:23
    
@Didier Piau : thank you very much for the answer. –  Rajesh D Apr 7 '11 at 10:04

1 Answer 1

up vote 3 down vote accepted

Let us use a general approach. A first principle to evaluate multiple sums is:

When dealing with multiple sums, see what happens when exchanging the order of the summations.

Re Q2, this means writing the sum $S$ as a sum over $x$ of $a(x)$ times a sum over $i$ and $j$.

Which brings us to a second general principle:

Sums over a fixed set of integers are easier.

And to the most useful tool to apply this principle:

Write the spans of sums as indicator functions.

In this context, some people use Iverson bracket $[\mathfrak A]$ to mean $1$ if assertion $\mathfrak A$ is true and $0$ otherwise, and I will use this convention. For instance, still Re Q2, $$ S=\sum_{j=0}^{N-1}\sum_{i=0}^{N-1}\sum_{x=0}^{N-1}[x\le \min\{i,j\}]\cdot a(x). $$ But $[x\le \min\{i,j\}]=[x\le i]\cdot[x\le j]$, hence exchanging the order of the summations yields $$ S=\sum_{x=0}^{N-1}a(x)\sum_{i=0}^{N-1}[x\le i]\sum_{j=0}^{N-1}[x\le j]. $$ The sum over $i$ and the sum over $j$ coincide and their common value is $$ \sum_{j=0}^{N-1}[x\le j]=\sum_{j=x}^{N-1}[x\le j]=N-x, $$ hence $$ S=\sum_{x=0}^{N-1}(N-x)^2a(x). $$ This solves Q2.

The solution for Q1 is somewhat more involved, but I suggest that you now see how far you can go with these principles to try to solve it.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.